Immunomodulatory effects of bone marrow-derived Mesenchymal stem cells on BALB/c mice model with induced Systemic lupus erythematosus (SLE): Effects of bone marrow-derived Mesenchymal stem cells - Khudhair Esmael, Ghassan; Rebai, Tarek; Gazar Chelab Al-Nailey, Khalil (Cellular and Molecular Biology, 2023)
Systemic lupus erythematosus (SLE) is an autoimmune inflammatory disease that causes acute inflammation in most body tissues. The current study aims to determine levels of some cytokines and chemokines in BALB/c mice with SLE and treatment by using BALB/c Mesenchymal stem cells (BM-MSCs). Forty BALB/c male mice were divided into four groups equally. The first and second groups received activated lymphocyte-derived DNA (ALD DNA) for induction of SLE. The second group received BM-MSCs/IV after the appearance of SLE clinical signs. The third group received BM-MSCs only, while the fourth group (control group) received PBS. All the study groups examine levels of IL-10, IL-6, TGFβ1, VEGF, CCL-2, CCL-5/RANTES, IFNγ, and ICAM -1 by ELISA kits. The cytokines levels are determined in all the study groups. There was a significant increase in ANA and anti-dsDNA levels in the first group, while there was a decrease in the second group (treatment by BM-MSCs). There is no significant difference between the third and control groups in ANA and anti-dsDNA levels. The first group showed a significant increase in IL-6, CCL-5/RANTES, VEGF, ICAM, CCL-2, and IFNγ levels and a decrease in IL-10 and TGFβ1. The second group showed low levels of IL-6, CCL-5/RANTES, VEGF, ICAM, CCL-2/MCP-1, and IFNγ but a high level of IL-10 and TGFβ1 as compared with the control group. The third group has no significant differences from the control group in all the tested parameters. BM-MSCs have an essential therapeutic role in the functional regulation of cytokines and chemokines in mice with SLE.